2023
DOI: 10.1186/s12877-023-04530-9
|View full text |Cite
|
Sign up to set email alerts
|

Technology for dementia care: what would good technology look like and do, from carers’ perspectives?

Ruth Brookman,
Simon Parker,
Leonard Hoon
et al.

Abstract: Background The development of technology in dementia care has largely been without consultation with carers, and has primarily focused on safety, monitoring devices, and supporting activities of daily living. Further, while involving end-users in the design of technology has been recommended, this is yet to become common practice. Method We conducted a mixed methods study with the aim of investigating carers’ values and priorities for technology de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…To the well-known areas of mobility, information and communication technology, biotechnology and ambient intelligence [ 50 ], the study at hand adds organizational and administrative tasks. In line with recommendations that technologies should complement face-to-face contact, not replace it [ 31 ], the stakeholder needs assessment points to a demand for information transfer and communication on ageing in place that could be met by technology. With older adults preferring counselling services and personal contacts to guide them through the system (e.g.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To the well-known areas of mobility, information and communication technology, biotechnology and ambient intelligence [ 50 ], the study at hand adds organizational and administrative tasks. In line with recommendations that technologies should complement face-to-face contact, not replace it [ 31 ], the stakeholder needs assessment points to a demand for information transfer and communication on ageing in place that could be met by technology. With older adults preferring counselling services and personal contacts to guide them through the system (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…In accordance to existing studies calling for problem-related solutions to be more effective in the long term [ 54 , 55 ], the stakeholders recommend supporting informal caregivers with help services and respite, and identifying which tasks can be performed by non-healthcare workers or solved by technological solutions. According to previous studies, technology can support the creation of meaningful social relationships [ 31 ], and is also desirable in professional care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants’ tendency to gravitate towards mainstream ICT confirms earlier studies, which reported that the multifunctionality and practicality of smartphones, tablet computers and videoconferencing applications enabled carers to balance their personal needs with those related to the person they care for ( Caprioli et al, 2023 ; Spann et al, 2022 ; Sriram et al, 2021 ). Also observed, was how unpaid carers turned to an array of improvised mainstream ICT solutions because they were mostly unaware of accessible and formal alternatives ( Brookman et al, 2023 ; Gibson et al, 2019 ; Sriram et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knapp et al (2015) and Sriram et al (2021) found that unpaid carers predominantly used household ICT devices such as telephones, televisions, MP3 players, and services including home Internet and online applications for monitoring, care coordination, reminiscence, entertainment and communication functions. Brookman et al (2023) surveyed unpaid carers’ use of GPS-enabled smartwatches, smartphones and digital picture frames for monitoring, reminder and reminiscence functions to support the care they provide. Gibson et al (2015) noted a trend amongst unpaid carers for linking GPS and camera devices to a tablet computer or a smartphone via WiFi Internet to monitor, supervise, and support the person they cared for.…”
Section: Introductionmentioning
confidence: 99%